2002
DOI: 10.2527/2002.804875x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of extruded kidney bean (Phaseolus vulgaris L. var. Pinto) and its effects on growth and skeletal muscle nitrogen fractions in rats

Abstract: The influence of extrusion cooking on the protein content, amino acid profile, and concentration of antinutritive compounds (phytic acid, condensed tannins, polyphenols, trypsin, chymotrypsin, alpha-amylase inhibitors, and hemagglutinating activity) in kidney bean seeds (Phaseolus vulgaris L. var. Pinto) was investigated. Growing male rats were fed diets based on casein containing raw or extruded kidney beans with or without methionine supplementation for 8 or 15 d. Rates of growth, food intake, and protein ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 0 publications
8
44
0
2
Order By: Relevance
“…The composition of raw and extruded chickpeas was similar to values presented by Khan et al (1995) and Marzo et al (2002). Extrusion cooking caused a significant decrease in moisture and ether extract contents.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The composition of raw and extruded chickpeas was similar to values presented by Khan et al (1995) and Marzo et al (2002). Extrusion cooking caused a significant decrease in moisture and ether extract contents.…”
Section: Discussionsupporting
confidence: 78%
“…Earlier experiments (Savage and Thompson, 1993;Savage et al, 1995) showed the possibility of reducing the effect of the ANF by various cooking and processing methods. Extrusion has been shown to be very effective in destroying lectins, protease inhibitors and α-amylase inhibiting enzymes (Marzo et al, 2002;Abd El-Hady and Habiba, 2003;Arija et al, 2006). Moreover, due to the presence of shear forces and high-energy input, proteins are more easily accessible for enzyme attack during the extrusion process (Camire, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ash content of wheat extrudates incorporated with legumes remains almost same were in the range of 11.5-15.9 g/kg. Marzo et al (2002) reported less influence of extrusion cooking in ash content.…”
Section: Effect On Nutritional Qualitymentioning
confidence: 92%
“…Parallel to the increased applications, interest has grown in the physico-chemical, functional and nutritionally relevant effects of extrusion processing. It also significantly reduces antinutrients present in legumes (Abd El Hady and Habiba 2003;Alonso et al 2000;Leontowicz et al 1999;Marzo et al 2002). Nutritional concern about extrusion cooking is reached at its highest level when extrusion is used specifically to produce nutritionally balanced or enriched foods, like weaning foods, dietetic foods, and meat replacers (Plahar et al 2003).…”
Section: Introductionmentioning
confidence: 99%